Answer:
60 Hope this helps you :)
Step-by-step explanation:
Answer:
y = -3x - 1
Step-by-step explanation:
y = mx + c
m = (-4-2)/(1-(-1)) = -6/2 = -3
y = -3x + c
When x = -1, y = 2
2 = -3(-1) + c
c = 2 - 3 = -1
y = -3x - 1
First, distribute the terms.
1(2x^3) = 2x^3
-1(x^2+11) = -x^2-11
Standard form:
2x^3 - x^2 - 11
Since there is a 3, the degree of polynomial is cubic.
Answer:
<em>2(15+8)</em>
Step-by-step explanation:
Given the expression 30+16
We are to use GCF to rewrite the sum as a product.
Get the factor of each value first as shown;
30 = 2 * 15
16 = 2 * 8
substitute the factors back into the expression:
30+16 = (2*15)+(2*8)
Since 2 is common to both terms, then:
30+16 = 2(15+8)
<em></em>
<em>Hence the required sum of product of the terms is 2(15+8)</em>